Development of Short Duration, Tolerance to High Temperature and Bipolaris Leaf Blight, and Moderately Susceptible to Blast Disease of Wheat Genotype with Trials in Various Agroecological Zones in Bangladesh - Alam, Mohammad Nur; HOSSAIN, MD. MONWAR; HAKIM, MD. ABDUL; ISLAM, MD. ZAHERUL; MAMUN, MD. ABDULLAH AL; ISLAM, RABIUL; AMIN, MOHAMMAD FARHAD; MUSTARIN, KISHOWAR-E-; EKRAM, MD. SARIFUL BIN; SHARMIN, SHAILA; ISLAM, MOHAMMAD SOHIDUL; AKTER, SAMIMA; et al. (International Journal of Scientific Research and Management (IJSRM), 2023)
Wheat production in Bangladesh faces to the detrimental effects of biotic and abiotic stresses that have been exacerbated by climate change. The development of short duration, high temperature and disease tolerant wheat variety is the most importance to produce higher yield combating the deleterious effects of the stresses. Some wheat lines (line was expressed by E) were evaluated at the different research stations of Bangladesh Wheat and Maize Research Institute (BWMRI) and farmers’ fields in consecutively three years under irrigated timely sowing (ITS) and irrigated late sowing (ILS) conditions. The days to heading (DH), days to maturity (DM), plant height (PH), spikelet spike-1 (SPS), grain spike-1 (GPS), thousand grain weight (TGW), and grain yield were depicted comparatively higher in ITS and ILS than ITS, but the severity of Bipolaris leaf blight (BpLB) and blast diseases were exhibited lower in BAW 1194 (E9) line than check varieties and other lines same conditions (BAW = Bangladesh Advanced Wheat). Those phenotypic and yield contributing characters, and BpLB and blast diseases were also observed lower in ILS than other genotypes.  Further, E9 exhibited the lower percentage of yield loss in the ILS compared to ITS than check and other genotypes indicated its high temperature tolerance. In addition, E9 exhibited relatively higher grain yield than other genotypes in the candidate variety demonstration and multiplication yield trials. Therefore, BAW 1194 line may be released as a short duration, tolerance to high temperature and BpLB, and moderately tolerance to blast disease wheat variety to accelerate wheat production.